Childhood vesiculobulous disorder (toxic epidermal necrolysis) in a resource constrained setting - Chapp-Jumbo, Assumpta Udechi; Ijeoma, Stella (Acta Biomedica Atenei Parmensis, 2021)
We report a case of childhood vesiculobulous disorder of the severity of Toxic Epidermal Necrolysis(TEN) in a 4 year ten month old female child resulting from caregiver prescribed medication. She is one of 4 children of a non consanguineous marriage with no family history of similar adverse drug reactions. She was initially managed in a private hospital before referral to our centre where we observed constraints of funds and crisis of confidence on the part of the parents. The need for enlightenment and counseling of care givers on cause of illness and advocacy for special funds for adverse drug events especially for indigent patients is hereby highlighted. Also the importance of optimization of available health care resources even in the midst of poor circumstances is emphasized.